Social and Territorial Endogamy in Dubrovnik: Matrimonial dispenses during the pontificates of Paul II and Sixtus IV (1464-1484) - Marinković, Ana (2005)
The paper is dealing with the supplications for matrimonial dispensation to the Holy Penitentiary arriving from the easten Adriatic coast, notably Dubrovnik. The overwhelming share of the material of Ragusan provenance is related to the strict practice of territorial and social endogamy in the Republic of Dubrovnik.
ENG